2006
DOI: 10.1258/135581906775094208
|View full text |Cite
|
Sign up to set email alerts
|

All dressed up but nowhere to go? Delayed hospital discharges and older people

Abstract: The evidence, as it currently stands, raises a number of issues about current hospital discharge policy, supporting some aspects of the current government agenda in England, but questioning other aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 0 publications
1
79
0
Order By: Relevance
“…Little analysis of these delays has been published recently, and there is considerable heterogeneity amongst older studies, many of which have methodological flaws. 8 Therefore, we performed an in-depth prospective study to define the causes and financial cost of delays in discharges from the general medical wards of a metropolitan teaching hospital. We show that the majority of patients experienced delays and that these delays interfered with the discharge of half the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Little analysis of these delays has been published recently, and there is considerable heterogeneity amongst older studies, many of which have methodological flaws. 8 Therefore, we performed an in-depth prospective study to define the causes and financial cost of delays in discharges from the general medical wards of a metropolitan teaching hospital. We show that the majority of patients experienced delays and that these delays interfered with the discharge of half the patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is scarce information regarding the non-English-speaking groups in previous studies. 1 We may speculate that these patients may have more communication problems with health professionals regarding their symptoms, complications or other ailments that may lead to delayed identification or treatment. However, it is also possible that more patients from an NESB were referred for discharge planning based on their medical problems.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Delayed discharge has become a major issue because it leads to unanticipated length of stay and bed block. 2,[5][6][7] Both the quality and cost-effectiveness of care may be compromised as a result.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent reviews have found the literature to be of poor quality, with a tendency to neglect patient and family perspectives. 51,52 The provision of rehabilitation services and residential care places, internal hospital processes, and co-ordination and communication with social care service processes and staff are all common causes of delay. This can be exacerbated by BACKGROUND, CONTEXT AND SCOPE discharge planning being delayed until the patient is ready for hospital discharge.…”
Section: Delayed Dischargesmentioning
confidence: 99%